Do Sex Workers Respond to Disease? Evidence from the Male Market for Sex - Shah, Manisha (American Economic Review, 2013)
Sex markets play a key role in the transmission of sexually transmitted infections (STI) and HIV/AIDS in developing countries. While individuals should substitute away from risky sex as STI prevalence rises, female sex workers draw a premium for engaging in unprotected sex, mitigating their propensity to use condoms. We provide the first evidence of a positive premium for non-condom sex in developing country male sex markets. Testing whether this is a compensating differential for disease risk, we find that a one percentage point increase in the STI rate increases the premium 28 percent. Market forces may curb the self-limiting effect of STI epidemics.